Leveraging Art to Support Refugee Newcomer Families’ Well-Being: A Qualitative Study - Dutton, Sherri; Davison, Colleen; Kou, Yu Jier (Refuge, 2025)
There has been a shift toward resettlement in smaller cities, creating potential new challenges, and opportunities, in supporting refugee families. This study used interviews and participant observation to explore health and social impacts of a settlement services–run arts-based therapy group for newcomer families in a small city. A social-ecological approach exploring how the program operated as a third space highlighted potential pathways for supporting newcomer families’ well-being across multiple levels. As a study exploring the intersection of refugee settlement, organizational programming, and well-being, this article contributes to a greater understanding of newcomer supports within a smaller city context.